Aegilops tauschii single nucleotide polymorphisms shed light on the origins of wheat D‐genome genetic diversity and pinpoint the geographic origin of hexaploid wheat. Issue 3 (4th February 2013) - Wang, Jirui; Luo, Ming‐Cheng; Chen, Zhongxu; You, Frank M.; Wei, Yuming; Zheng, Youliang; Dvorak, Jan
Summary Hexaploid wheat (Triticum aestivum, genomes AABBDD) originated by hybridization of tetraploid Triticum turgidum (genomes AABB) with Aegilops tauschii (genomes DD). Genetic relationships between A. tauschii and the wheat D genome are of central importance for the understanding of wheat origin and subsequent evolution. Genetic relationships among 477 A. tauschii and wheat accessions were studied with the A. tauschii 10K Infinium single nucleotide polymorphism (SNP) array. Aegilops tauschii consists of two lineages (designated 1 and 2) having little genetic contact. Each lineage consists of two closely related sublineages. A population within lineage 2 in the southwestern and southern Caspian appears to be the main source of the wheat D genome. Lineage 1 contributed as little as 0.8% of the wheat D genome. Triticum aestivum is subdivided into the western and Far Eastern populations. The Far Eastern population conserved the genetic make‐up of the nascent T. aestivum more than the western population. In wheat, diversity is high in chromosomes 1D and 2D and it correlates in all wheat D‐genome and A. tauschii chromosomes with recombination rates. Gene flow from A. tauschii was an important source of wheat genetic diversity and shaped its distribution along the D‐genome chromosomes.